E-Proceedings of 4th International Conference of Media and Society (ic-MAS2022) : communicating cultural heritage - Faidz Felani, Majeri; Ting, Su Hie; Vimala, Govindaraju (2024)
1. Application of Propaganda Techniques by Barisan Nasional in Malacca’s State Election 2021 Faridah Dahalan, Ahmad Rizalman Jamal, Kamarul Ariffin, Amalina Jemail & Shamsiah Abd Kadir 1 2. Could National Museums in Malaysia Provide Varieties of Storytelling on Malay Ethnicities? Yi-Chang Chang & Noor Azmira Mohamed 14 3. Enhancing Brand Love via Branding Architecture Among Telecommunication Service Provider Users Al Amirul Eimer Ramdzan Ali, Nurzali Ismail & Ahmad Syahmi Ahmad Fadzil 20 4. Usage of Social Media Related to Muslim Friendly Hospitality Tourism among Users Rosninawati Hussin, Norhayati Rafida Abdul Rahim, Safiyyah Ahmad Sabri & Ahmad Ihab Uwais 32 5. Investigating Influencing Factors of EFL Preservice Teachers' Identity Construction in Rural Areas Kunto Nurcahyoko, Wanda Giovani & Elisabet Nanda Ayu 46 6. Hypercorrection among Native Speakers of Bidayuh Biatah when Speaking English Leonardo Ginyun 57 7. Social Media Usage by Book Publishers in Nigeria: A Social Strategy Cone Perspective Abdulrasheed A. Afolabi & Izzal Asnira Zolkepli 68 8. Intangible Cultural Heritage and Cultural Knowledge: A Study on the Bidayuh Folktales, Dondan Yvonne Michelle Campbell 80 9.